Contralateral Regional Recurrence in Lateralized or Paramedian Early-Stage Oral Cancer Undergoing Sentinel Lymph Node Biopsy—Comparison to a Historic Elective Neck Dissection Cohort - Mahieu, Rutger; den Toom, Inne J.; Boeve, Koos; Lobeek, Daphne; Bloemena, Elisabeth; Donswijk, Maarten L.; de Keizer, Bart; Klop, W. Martin C.; Leemans, C. René; Willems, Stefan M.; Takes, Robert P.; Witjes, Max J. H.; et al. (Frontiers in Oncology, 2021)
Introduction: Nowadays, two strategies are available for the management of the clinically negative neck in early-stage (cT1-2N0) oral squamous cell carcinoma (OSCC): elective neck dissection (END) and sentinel lymph node biopsy (SLNB). SLNB stages both the ipsilateral and the contralateral neck in early-stage OSCC patients, whereas the contralateral neck is generally not addressed by END in early-stage OSCC not involving the midline. This study compares both incidence and hazard of contralateral regional recurrences (CRR) in those patients who underwent END or SLNB. Materials and Methods: A retrospective multicenter cohort study, including 816 lateralized or paramedian early-stage OSCC patients, staged by either unilateral or bilateral END (n = 365) or SLNB (n = 451). Results: The overall rate of occult contralateral nodal metastasis was 3.7% (30/816); the incidence of CRR was 2.5% (20/816). Patients who underwent END developed CRR during follow-up more often than those who underwent SLNB (3.8 vs. 1.3%; p = 0.018). Moreover, END patients had a higher hazard for developing CRR than SLNB patients (HR = 2.585; p = 0.030). In addition, tumor depth of invasion was predictive for developing CRR (HR = 1.922; p = 0.009). Five-year disease-specific survival in patients with CRR was poor (42%) compared to patients in whom occult contralateral nodal metastases were detected by SLNB or bilateral END (88%), although not statistically different (p = 0.066). Conclusion: Our data suggest that SLNB allows for better control of the contralateral clinically negative neck in patients with lateralized or paramedian early-stage OSCC, compared to END as performed in a clinical setting. The prognosis of those in whom occult contralateral nodal metastases are detected at an earlier stage may be favorable compared to those who eventually develop CRR, which highlights the importance of adequate staging of the contralateral clinically negative neck.